2018
DOI: 10.1038/s41598-018-25570-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of first-line and second-line terlipressin versus sole norepinephrine in fulminant ovine septic shock

Abstract: The Surviving Sepsis Guidelines suggest the use of vasopressin in case of catecholamine-refractory septic shock. Terlipressin (TP) as a V1-selective AVP analogue is a potential alternative, though data regarding the first-line administration in septic shock are scarce. The present study explored and compared the effects of first-line vs. second-line infusion of TP or sole norepinephrine regarding organ function, fluid and norepinephrine requirements and survival in fulminant ovine septic shock. Peritoneal seps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…To this end, comprehensive nursing has been identified for complication prevention of the lower extremities to potentiate the efficacy of norepinephrine; nonetheless, the expected treatment outcome is somehow compromised [ 8 , 9 ]. Previous studies have found that in the treatment of the skin radiation injury of breast cancer patients during radiotherapy [ 10 , 11 ], the collagen antibacterial functional dressing accelerated cell metabolism, promoted wound healing, relieved skin pain, and regulated the level of local inflammatory factors, which is conducive to injured skin repair. Accordingly, this study was designed to explore the effectiveness of collagen antibacterial functional dressing plus continuous care on the skin injury of lower extremities caused by norepinephrine in patients with septic shock.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, comprehensive nursing has been identified for complication prevention of the lower extremities to potentiate the efficacy of norepinephrine; nonetheless, the expected treatment outcome is somehow compromised [ 8 , 9 ]. Previous studies have found that in the treatment of the skin radiation injury of breast cancer patients during radiotherapy [ 10 , 11 ], the collagen antibacterial functional dressing accelerated cell metabolism, promoted wound healing, relieved skin pain, and regulated the level of local inflammatory factors, which is conducive to injured skin repair. Accordingly, this study was designed to explore the effectiveness of collagen antibacterial functional dressing plus continuous care on the skin injury of lower extremities caused by norepinephrine in patients with septic shock.…”
Section: Introductionmentioning
confidence: 99%
“…First is due to the small sample size that limited the precision of the overall review. Second, we didn't conduct a subgroup meta-analysis based on the different timing of TP usage, since there were only some studies performed on animals (Asfar et al, 2005;Kampmeier et al, 2018) and case series (Zeballos et al, 2006;Morelli et al, 2007).…”
Section: Strengths and Limitationsmentioning
confidence: 99%